Implementation of the Exemplary Method in Forming the Morals and Character of Class VII Students at SMP IT Ar Rojaq - M. Fadli Ritonga; Basyarul Ulya; Betti Megawati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study aims to determine how the application of the exemplary method in shaping the morals and character of grade VII students at SMP IT Ar Rojaq. The research method used is descriptive qualitative, with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that teachers at SMP IT Ar Rojaq actively apply the exemplary method in the educational process, both through attitudes, speech, and real actions in everyday life in the school environment. The exemplary behavior shown by teachers includes aspects of discipline, honesty, responsibility, politeness, and social concern. From the results of statements given to students as many as 50 respondents, it was found that exemplary behavior had a very good effect of up to 90%. The impact of implementing this method can be seen in changes in student behavior that are better in terms of morals and character. Supporting factors for the success of implementing this exemplary method include teacher commitment, a conducive school environment, and ongoing character development. Thus, the exemplary method has proven to be effective as a strategy in shaping students' morals and character, and can be used as the main approach in education based on Islamic values